2021
DOI: 10.31219/osf.io/hgxwn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Competence of future teachers in the digital security area

Abstract: Technology and Internet use poses digital security problems and risks. This article presents the results of a study evaluating the digital competence of preservice teachers within the DigCompEdu European framework. A group of 317 undergraduates from Spain and Portugal completed a 59-item questionnaire validated by experts to assess the level and predominant competence profile in initial training (including knowledge, uses and interactions, and attitudinal patterns). The results show that 47% of the participant… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
2
0
1
Order By: Relevance
“…In general, the results of these articles indicate that teachers do not feel sufficiently confident they have the necessary digital teaching competencies. This result is consistent with other studies that suggest the teachers need training in the necessary digital skills (Gallego-Arrufat, 2019;Tárraga-Mínguez et al, 2021) Thought is needed regarding developing a framework or a model for the digital competencies for Saudi teachers. That framework or model should consider the culture and local environment with all their aspects and should be adopted by colleges of education which are responsible for preparing future teachers.…”
Section: Discussionsupporting
confidence: 90%
“…In general, the results of these articles indicate that teachers do not feel sufficiently confident they have the necessary digital teaching competencies. This result is consistent with other studies that suggest the teachers need training in the necessary digital skills (Gallego-Arrufat, 2019;Tárraga-Mínguez et al, 2021) Thought is needed regarding developing a framework or a model for the digital competencies for Saudi teachers. That framework or model should consider the culture and local environment with all their aspects and should be adopted by colleges of education which are responsible for preparing future teachers.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, we have the study by Burgos-Torre and Salas-Blas (2020), who concluded that self-efficacy has a direct correlation with academic self-regulation and an inverse correlation with procrastination. Gallego, Torres and Pessoa (2019), evidenced in their study a good performance around digital competence, where the significant of their research is the conclusion they reach regarding lower order thinking skills, which demands a higher tendency of students than higher order thinking skills, the same that presents a lower assiduity. Flores-Lueg and Roig-Vila (2019), conducted a research where the results show that it is the males who consider that they have more knowledge in the management of ICT than the females.…”
Section: Self-efficacy and Digital Competence In University Studentsmentioning
confidence: 88%
“…This leads to wonder why higher education places such a high priority on digital security specifically in the framework of teacher training programs? Most research on digital literacy, in fact, focus on technological and informational dimensions and few address the need of imparting courses on digital security to future teachers [11], [12], [13] even though it is of essence to teacher training programs [14]. Furthermore, as digital security is viewed as crucial among the Global Skills index [15], higher education should prioritize it through training and holistic approaches [11] [12].…”
Section: Introductionmentioning
confidence: 99%